A new way of teaching an old subject: Pharmacy Law and Ethics - S Chetty; V Bangalee; F Oosthuizen (South African Medical Association, 2018)
Background. Pharmacy educators are responsible for ensuring that students are equipped with the necessary regulatory knowledge required to deal with ethical challenges that arise in practice. Teaching methods have a strong impact on student learning, making it essential to determine how learning is influenced when changing pedagogy.Objective. To describe students’ experience and perceptions of the use of a case-based learning (CBL) activity as an adjunctive method to didactic teaching of pharmacy law and ethics.Method. A survey was conducted among 3rd-year pharmacy students enrolled for a Pharmacy Law and Ethics course at the University of KwaZulu- Natal, Durban, South Africa. The course content was delivered didactically, followed by a CBL activity for which the students were divided into groups and assigned various real-life case studies.Results. Most of the 74 respondents (66%) agreed that the activity was enjoyable and metacognitively useful. A majority (77%) found the activity interactive, and 92% agreed that it enhanced their understanding of pharmacy law concepts. Eighty percent agreed that it facilitated their understanding of law and ethics concepts, and their application to real-life situations.Conclusion. The use of CBL was beneficial to both the individual student’s learning experience and the overall class learning process. More importantly, the exercise improved their metacognitive awareness, and suggests the need to consider this method of teaching as part of the formal curriculum to better equip students to deal with ethical issues that will arise in practice.